Dyke Swarms:Keys for Geodynamic Interpretation Keys for Geodynamic Interpretation - Srivastava, Rajesh K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Dykes occur in a wide variety of geological and tectonic settings and their detailed study through space and time is imperative for understanding several geological events. Dykes are believed to be an integral part of continental rifting and when they occur as spatially extensive swarms of adequate size can be of immense utility in continental reconstructions. This also helps to identify Large Igneous Provinces (LIPs). It is also well acknowledged that the continental flood basalts and major dyke swarms have their origin related in some way to the up-rise of hot mantle plumes which may lead to rifting and eventual continental break-up. Dykes signify crustal extension and are important indicators of crustal stabilisation events, supercontinental assembly and dispersal, crust-mantle interaction and play a significant role in the delineation of crustal provinces as well as in deciphering crustal evolution events. Many economic mineral deposits of the world are also associated with a variety of dykes. The volume will provide state-of-the-art information on all aspects of dykes with emphasis on the origin, evolution and emplacement of dykes.
Part 1 Geosimulation and land use plan -- 1. Methodology of urban growth simulation -- 2. Geosimulation model using geographic automata for simulating land use patterns in urban partitions -- 3. GeoSimulation and land use control of urban boundary -- 4. Spatial and institute constraint reflecting land use policy in urban growth simulation -- 5. Indentification of polilcy parameters for planned form of urban land use using constrained CA -- 6. Urban growth simulation for spatial strategic plan of Chuangdong area -- 7. A MAS simulation approach for visualizing the impact of land use policy on shopping location regulation -- Part 2 Geo-Visualization and urban design -- 8. Methodology of on-line visualization -- 9. An online tool of park design game and public participation -- 10. Consensus of design guidelines using vsualization tool of townscape design -- 11. Design learning using online design tool for reconstruction of traditional house -- 12. Online meeting delilberation -- virtual reality for planning committee -- Part 3 Geography information system and planning support -- 13. Methodology of planning support system using GIS -- 14. A decision support tool for retrieving planning alternative of historical conservation area from spatial data using GIS -- 15. Retrieve district ecological network from aero photograph and envrionmental learning -- 16. CASGIS as planning support system using GIS -- 17. Visualization of Usable Building Space According to Planning Permission Ordinances in Japan -- 18. Integration of MAS and GIS using Netlogo.
Keywords: Geography; Geology; Physical geography; Sedimentology; Earth Sciences; Geophysics/Geodesy.; Sedimentology; Geology